Acronyms, initialisms & abbreviations dictionary a guide to acronyms, abbreviations, contractions, alphabetic symbols, and similar condensed appellations - Hall, Linda D.; Gale Group (Detroit, Michigan Gale, 2008)
Provides definitions of a wide variety of acronyms, initialisms, abbreviations and similar contractions, translating them into their full names or meanings. Terms from subject areas such as associations, education, the Internet, medicine and others are included.
vol. 1. A-C -- vol. 2. D-I -- vol. 3. J-P -- vol. 4. Q-Z.
"ISSN 0270-4404."
Electronic reproduction.
Keywords: Acronyms -- Dictionaries; Abbreviations -- Dictionaries; Initials -- Dictionaries; Electronic books